Розробка алгоритму пошуку несправності блока живлення - Калищук, А. А. (ХНУРЕ, 2019)
The source of feed behaves to the apparatus that is exposed to enhanceable mechanical influences in investigation what to not й must be made great demand on reliability the high level of repairability is provided in particular. As a result of the conducted work methodology of finding out disrepairs is got in the ana-lysable power module